Readiness of Local Governments in the Application of Accrual-Based Accounting Standards - Atang Hermawan (SEAN Institute, 2023)
Major modifications were made to the financial reporting system in Indonesia after the passage of Law Number 71 of 2010 concerning accrual-based Government Accounting Standards (SAP). It is hoped that these alterations will allow for a more accurate depiction of financial standing, the presentation of accurate data on rights and obligations, and the ability to more accurately gauge performance. The purpose of this research is to ascertain whether or not local governments are prepared to switch to a more rigorous system of accounting based on accruals. Descriptive qualitative research describes this kind of study. The objects were collected from the Pangandaran Regency Regional Government for this study. According to the findings, different trainings have been provided by the Pangandaran district government as part of the district's implementation of accrual-based SAP. This is supported by a government legislation that mandates the use of accrual-based SAP by all subnational administrations, including the government of the Pangandaran Regency. There is a lack of human resources and training in preparation for the use of accrual-based accounting standards, such as the still-manual preparation of LKPD.